STRATEGI TERKINI DALAM PENDIDIKAN KEPELATIHAN OLAHRAGA: MEMBANGUN PELATIH UNGGUL DI ERA DIGITAL - M Torero Rigel Centeury; Hendri Mulyadi; Nanda Dwicahya; Rahmat Syaifudin; Muhammad Rifai; Singgih Prastawa (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
The development of digital technology has brought significant changes in various aspects of life, including in sports coaching education. Coaches are required to adapt to the latest strategies to improve training effectiveness and athlete development. This article discusses modern strategies in sports coaching education, including the utilization of digital technology, data-driven approaches, and innovations in training methods. Digital transformation allows coaches to access and analyze athlete performance data in real-time, utilize artificial intelligence in decision-making, and optimize communication and learning through digital platforms. In addition, sport psychology-based approaches and adaptive leadership are important aspects in building excellent coaches in the digital era. The results show that coaches who adopt digital strategies tend to be more effective in improving athlete performance, optimizing training planning, and adjusting learning methods according to individual needs. Thus, sports coaching education must continue to innovate in integrating the latest technology and approaches to create competitive and superior coaches in the digital era.